Can the Tenure of the Government of National Unity Enhance Public Accountability in the South African Government? (2024-2029) - Thusi, Xolani (Administrative and Environtmental Law Review, 2024)
The South African government has struggled with public accountability over the past 30 years of democracy. The government has been dominated by the African National Congress (ANC) for 30 years, and this dominance has not enhanced public accountability but has made it worse. It cannot be argued that the government led by ANC has made many strides in advancing the lives of the marginalised people through progressive policies that were designed to address the wrongs made by the apartheid government. Overtime the government led by ANC abandon it principles and values and this is evident as this government high ranking political office bears were mostly caught up in corruption scandals. The state capture masterminds were mostly affiliated with the ANC, and this shows a lack of public accountability, and the bunts are mostly felt by the marginalised people. As the lack of public skyrocketed all spheres and entities of South Africa government this led to poor public service delivery across the public sector. The lack of public service delivery is evident in South African government as service delivery protest takes place more often mostly in the local government sphere which is closer to the people. This paper analysed the prospects of the GNU in enhancing public accountability in South African public sector. The author is of the view that the GNU has the potential to enhance public accountability and service delivery in South Africa, due to diverse political parties working together in cabinet and in the parliament. A desktop approach was used to review recent literature on the phenomenon.